"Never Say Never?" Heterosexual, Bisexual, and Lesbian Women's Accounts of Being Childfree. (December 2019) - Hayfield, Nikki; Terry, Gareth; Clarke, Victoria; Ellis, Sonja
Feminist scholars have identified a "motherhood imperative" in Western cultures, when heterosexual women are understood to both want and to have children. However, social shifts have resulted in a decrease in pronatalism as well as an increase in social recognition of the parenting desires of same-sex parents. Despite a resurgence of interest in childfree identities, research to date has predominantly focused on heterosexual women's explanations for being childfree and their experiences of marginalization. Our aim in the current study was to explore how childfree heterosexual, lesbian, bisexual, and queer women negotiate their childfree lives and identities in the context of their personal and social relationships within changing cultural contexts. Data from 23 interviews with women in the United Kingdom, who responded to a call for childfree participants, were thematically analyzed. We constructed two themes: (1) Never say never? Negotiating being childfree as ever precarious, which shows how women constructed being childfree as requiring constant revisiting and renegotiating to maintain and (2) An ordinary life: Constructing being childfree as rational and reasonable, in which we identify the rhetorical efforts of participants to establish their being childfree as an ordinary, reasonable, and rational position. We conclude that for these women, childfreedom was constantly in flux and that maintaining a positive childfree identity required considerable identity work in order to manage intimate personal relationships and wider friendships. Online slides for instructors who want to use this article for teaching are available on PWQ 's website athttp://journals.sagepub.com/page/pwq/suppl/index